Fragility of epidermis: acne and post‐procedure lesional skin. (14th August 2017) - Fabbrocini, G.; Rossi, A.B.; Thouvenin, M.‐D.; Peraud, C.; Mengeaud, V.; Bacquey, A.; Saint Aroman, M.
Abstract: 'Fragile skin', or skin with lower resistance to aggressors, can be broadly classified into four causal categories: constitutional (age‐dependent or associated with specific vulnerable locations on the body, e.g. eyelids), pathological (related to disease), circumstantial (related to environmental or internal factors, e.g. stress) and iatrogenic (caused by medical interventions or treatments). In this supplement, we focus on the fourth category, the iatrogenic origin of fragile skin and the role that dermo‐cosmetics can have in restoring the natural protective function of the skin following treatments for skin diseases and medical interventions. We present epidemiological data on the prevalence of fragile skin in three different geographical regions, and the results of two randomized controlled studies investigating the efficacy and tolerability of dermo‐cosmetics in combination with topical acne treatment and following physical skin damage. Overall, we found that prevalence across the three regions (23% in Germany, 41% in UAE, 56% in Taiwan) reflected previous global estimates (24–53%) across skin types, with significant associations found with environmental and lifestyle factors, such as stress, humidity and pollution. The iatrogenic effects of topical acne treatments can result in poor compliance or use of over‐the‐counter moisturizers, which may reduce treatment efficacy. Dermo‐cosmetics were found to aid in restoration of fragile skin caused by the acne topical retinoid treatment adapalene 0.1% gel, by reducing transepidermal water loss and improving skin hydration, as well as reducing the side‐effects such as skin irritation that are frequently associated with topical retinoids. Additionally, dermo‐cosmetic products were found to accelerate wound closure following skin damage in a laser ablation model and reduced the duration of post‐procedural side‐effects such as itching and burning.